2022
DOI: 10.3390/ani12030311
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Improves Intestinal Morphology and Anti-Oxidation Ability in Deoxynivalenol-Challenged Piglets

Abstract: This study aimed to investigate the potential effects of resveratrol (RES) on intestinal function and oxidative stress in deoxynivalenol (DON)-challenged piglets. Twenty-four healthy Duroc × Yorkshire × Landrace weaned piglets at the age of 28 ± 1 days were randomly divided into four groups with six repetitions per group. The four groups were as follows: the control group (CON), fed with a basic diet; the RES group, fed with a basal diet + 300 mg/kg RES; the DON group, fed with a basal diet containing 2.65 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…We found that the addition of RES could increase the villus height, and alleviate the intestinal morphological damages induced by LPS, thus improving the intestinal mucosa integrity in yellow-feathered broilers. These results are consistent with previous studies on the protective effect of RES on intestinal morphology and structure ( Liu et al, 2016 ; Zhuang et al, 2021 ; Hong et al, 2022 ). Moreover, the intestine mucosal barrier represents the first line of the host defence against invading enteric pathogens and toxins, which plays key roles in nutrient digestion and absorption ( Turner, 2009 ).…”
Section: Discussionsupporting
confidence: 93%
“…We found that the addition of RES could increase the villus height, and alleviate the intestinal morphological damages induced by LPS, thus improving the intestinal mucosa integrity in yellow-feathered broilers. These results are consistent with previous studies on the protective effect of RES on intestinal morphology and structure ( Liu et al, 2016 ; Zhuang et al, 2021 ; Hong et al, 2022 ). Moreover, the intestine mucosal barrier represents the first line of the host defence against invading enteric pathogens and toxins, which plays key roles in nutrient digestion and absorption ( Turner, 2009 ).…”
Section: Discussionsupporting
confidence: 93%
“…The morphological changes in intestinal tissue may be a direct reflection of how well the intestinal barrier is functioning. Intestinal VH, CD, and VH/CD are crucial indicators of intestinal mucosal morphology [ 25 , 26 ]. Disaccharides need to be further broken down into monosaccharides by intestinal mucosal cells (such as sucrase, lactase, and maltase) in order to be absorbed, because intestinal epithelial cells cannot do this directly.…”
Section: Discussionmentioning
confidence: 99%
“…Pigs, the most sensitive species to DON, are often at high risk of exposure to DON because corn and wheat are common high-proportion ingredients in their formulated feed [ 21 ]. The intestine has been authenticated as one of the most crucial targets of DON exposure [ 11 , 12 ].…”
Section: Don-induced Enterotoxicity In Swinementioning
confidence: 99%